Masters of the 20th Century : 1946-1971 Marlborough Twenty-five Years. (New York : Marlborough Gallery Inc., 1971)
Arp, Bacon, Balla, Beckman, Braque, Chagall, Derain, Dubuffet, Ernst, Feininger, Gabo, Giacometti, Gottlieb, Heckel, Jawlensky, Johns, Kirchner, Klee, Kline, Lipchitz, Lipton, Magritte, Moore, Motherwell, Nicholson, Nolde, Pevsner, Picasso, Polllock, Reinhardt, Rodin, Rothko, Schwitters, Signac, Smith, Soutine, Still, Sutherland, Utrillo, Vlaminck, Vuillard
boek